Preserving memory in Minoan Crete Filled-in bench and platform deposits from the First Palace of Phaistos - Caloi, Ilaria (Journal of Greek Archaeology, 2017)
Recent studies in Aegean prehistory have started to deal more intensively with the practice of accumulated artefacts in structured depositions and to see these as mnemonic records, reflecting people’s desire to preserve the memory of some specific events.